Pengaruh Promosi Penjualan, Iklan, Sosial Media Marketing dan Celebrity Endorsement Terhadap Ekuitas Merek Produk Sabun Pembersih Wajah Pond’s pada Generasi Z di Kabupaten Pati. - Alya Zakiatunafisah; Dina Lusianti; Sutono (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of sales promotion, advertising, social media marketing and celebrity endorsement on brand equity. The object of this study is Pond's facial cleanser in Pati Regency. The sampling technique used purposive sampling with the Lemeshow formula, resulting in a sample of 100. The analysis tool in this study used the IBM SPSS version 25 application. The results of this study indicate that sales promotion has a positive and significant effect on brand equity, advertising has a positive and significant effect on brand equity, social media marketing has a positive and significant effect on brand equity, celebrity endorsement has a positive and significant effect on brand equity. Simultaneously, sales promotion, advertising, social media marketing and celebrity endorsement have a significant effect on brand equity of Pond's products.